2019
DOI: 10.1111/sms.13466
|View full text |Cite
|
Sign up to set email alerts
|

Chronic anterior tibial stress fractures in athletes: No crack but intense remodeling

Abstract: Purpose Delayed healing of anterior tibial stress fractures in athletes is related to high tensional forces acting across a putative fracture gap. These forces lead to crack propagation and create strains that exceed tissue differentiation thresholds for new bone to form in the gap. The “dreaded black line” is a radiographic hallmark sign of stress fractures considered to represent a transverse fracture gap. However, whether a fracture gap truly exists at the microscopic level remains unclear. The aim of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 28 publications
(68 reference statements)
0
12
0
Order By: Relevance
“…The relationships between acute changes in markers of bone formation and resorption in response to LEA and longterm bone health are unclear. Sustained and localized acceleration of bone remodeling may play a role in the pathogenesis of bone stress injury in athletes [82,83]. However, bone (re)modeling markers are typically measured systemically and, therefore, any change in the balance of such markers does not necessarily reflect a change in bone remodeling at a specific site.…”
Section: Effects Of Short-term Low Energy Availability and Impact Exementioning
confidence: 99%
“…The relationships between acute changes in markers of bone formation and resorption in response to LEA and longterm bone health are unclear. Sustained and localized acceleration of bone remodeling may play a role in the pathogenesis of bone stress injury in athletes [82,83]. However, bone (re)modeling markers are typically measured systemically and, therefore, any change in the balance of such markers does not necessarily reflect a change in bone remodeling at a specific site.…”
Section: Effects Of Short-term Low Energy Availability and Impact Exementioning
confidence: 99%
“…However, only a small number of studies have reported the clinical course of pseudofracture healing in response to asfotase alfa in adult patients with infantile-, pediatric- or adult-onset HPP. The pseudofracture typically developed in the immaturely mineralized bone tissue, and the detailed evaluation of the pseudofracture in pediatric-onset HPP under treatment with asfotase alfa, using three-dimensional cone-beam computed tomography, indicated the pathophysiologic changes of the remineralization in the osteoid tissue ( Schilcher et al, 2019 ; Stürznickel et al, 2021 ). Rolvien et al assessed the healing course of fracture in adults with infantile-onset HPP under treatment with asfotase alfa by several modalities, including physical function tests, magnetic resonance imaging (MRI), and dual-energy X-ray absorptiometry ( Rolvien et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…More persistent ROD associated with deep penetration of the cortical bone along phalanges is like cavitated caries. In addition, noncavitated caries are morphologically similar to resorption cavities during bone remodeling [2,3,30] or the osseous radiolucencies defined as traumatic cysts [31].…”
Section: Infectionsmentioning
confidence: 99%
“…From a physiologic perspective, WSLs are localized pathologic processes (caries) that may or may not be active [83]. From an osseous perspective, a WSL is analogous to some manifestations of negative calcium balance, i.e., accelerated bone remodeling [30] or relatively quiescent bone cysts [31]. It is clear that bones and teeth are susceptible to severe destruction in the presence of sustained demineralization.…”
Section: Detection and Assessment Of White Spotsmentioning
confidence: 99%